2019
DOI: 10.1103/physrevlett.123.030603
|View full text |Cite
|
Sign up to set email alerts
|

Heating-Induced Long-Range η Pairing in the Hubbard Model

Abstract: We show how, upon heating the spin degrees of freedom of the Hubbard model to infinite temperature, the symmetries of the system allow the creation of steady states with long-range correlations between η-pairs. We induce this heating with either dissipation or periodic driving and evolve the system towards a non-equilibrium steady state, a process which melts all spin order in the system. The steady state is identical in both cases and displays distance-invariant off-diagonal η correlations. These correlations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 58 publications
(101 reference statements)
3
82
4
Order By: Relevance
“…As discussed in section 2.2 this symmetry in the imaginary modes is seen for local, translationally-invariant dephasing in an interacting system [25,31]. Hence, the system will undergo completely nonlinear response to peturbations away from the dynamical symmetry regime.…”
Section: Perturbations Away From the Dynamical Symmetry Regimementioning
confidence: 87%
See 2 more Smart Citations
“…As discussed in section 2.2 this symmetry in the imaginary modes is seen for local, translationally-invariant dephasing in an interacting system [25,31]. Hence, the system will undergo completely nonlinear response to peturbations away from the dynamical symmetry regime.…”
Section: Perturbations Away From the Dynamical Symmetry Regimementioning
confidence: 87%
“…Consequently, the system will be perfectly synchronised as all the bodies in the system will be locked to the same frequency and phaseindependent of the specific value of any microscopic parameters. Recent work has shown that the interplay between interactions and local, homogeneous dephasing in an open quantum system can 'wash' out any geometry associated with the system: creating steady states with offdiagonal long-range order and ensuring they, along with any strong dynamical symmetry operators, are completely translationally symmetric (see [25,31]). These states and operators form a complete basis for the long-time density matrix of the system.…”
Section: Quantum Synchronisation Via Dynamical Symmetries Interactiomentioning
confidence: 99%
See 1 more Smart Citation
“…The Hubbard model has a rich symmetry structure which has made it a natural environment for inducing exotic non-equilibrium phases through dissipation [52,53].…”
Section: Hubbard Modelmentioning
confidence: 99%
“…(10)- (11). This points to the importance of the role of charges in realistic non-equilibrium processes, such as equilibration in quasi-integrable systems [24], and dissipation and relaxation in driven systems with conservation laws [42,43]. A case of particular theoretical interest for future exploration arises when the charges supported by the Hamiltonian do not commute with each other [25,[44][45][46][47].…”
Section: Resultsmentioning
confidence: 99%